Síntese de nanopartículas de ouro por precipitação - Weber, Alfredo dos Santos (Universidade Federal de São Carlos, 2012)
Gold nanoparticles have properties with great interest in applications in biomedicine, catalysis, optics and electronics. This study seeks to produce stable, size-homogeneous and well-dispersed particles. The chosen method is the reduction of metallic ions by organic salts in aqueous medium. The organic compounds act as stabilizers and their interactions with the metallic surface defines the particles final characteristics. Sodium citrate was tested as reducing agent. The influence of operational parameters such as temperature, acidity, stoichiometric relations in the nucleation, growth process and size particle was tested. Spectroscopy of UV-visible, scanning and transmission electron microscopy were used as characterization technics. It was concluded that increasing the temperature the particle size and the standard deviation decrease and the produced particles are more uniform in morfology. The nucleation is favored for higher temperatures of reaction, for lower acidity and higher concentration of sodium citrate solution. The particles are formed by clusters which agglomerate and nanowires that incorporate into the face centered cubic crystal structure. UV spectroscopy was efficient in evaluating qualitatively the reaction development and the growth of particles. And with that technique it was observed that transverse polarization of the particles was predominant. The reaction conditions temperature of 80ºC, initial pH of the citrate sodium solution in 8 and 10 e molar relations about 5 produced particles with narrow size distribution and 17 nm of median diameter.
Keywords: Cristalização; Microscopia eletrônica; Ressonância plasmon; Método dos momentos; Colóide Nanopartículas; Ouro; Nanotecnologia; Precipitação; Nanoparticles; Crystallization; Gold; Nanotechnology; Precipitation; Colloid; ENGENHARIAS::ENGENHARIA QUIMICA